2022
DOI: 10.3390/cancers14122971
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Systematic Analysis of Driver Mutations’ Prevalence in Early- and Advanced-Stage NSCLC: Implications for Targeted Therapies in the Adjuvant Setting

Abstract: The approval of osimertinib for adjuvant treatment of stage I–II–III EGFR-mutated NSCLC (early stage) represents a paradigm shift, raising the question of whether other genotype-matched therapeutics approved for advanced-stage NSCLC can also provide clinical benefit in the adjuvant setting. However, there is a paucity of real-world data on the prevalence of actionable genomic alterations (GAs) in early-stage NSCLC. We used next-generation sequencing, complemented by immunohistochemistry and fluorescence in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In our present analysis, our focus was directed at clinical stage I NSCLC including the squamous histology. We meticulously examined both histological and clinical factors that are readily accessible within routine medical practice (16). However, looking ahead, it is imperative to delve further into this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…In our present analysis, our focus was directed at clinical stage I NSCLC including the squamous histology. We meticulously examined both histological and clinical factors that are readily accessible within routine medical practice (16). However, looking ahead, it is imperative to delve further into this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are limited data on the specific types of EGFR mutations and co-mutations in early-stage NSCLC [ 22 , 35 , 36 , 37 , 38 , 39 , 40 ]. Studies of NSCLC in advanced stages (IIIB–IV) have shown that both the type of mutation (common or rare mutations, compound mutations, primary resistant mutations) and co-occurring mutations have an impact on prognosis and response to TKI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As much as we know about the genomic landscape and antitumor immune response in advanced-stage NSCLC, little has been published on the prevalence and nature of EGFR mutations and other driver alterations and PD-L1 expression in early-stage NSCLC [ 22 , 35 , 36 , 37 , 38 , 39 , 40 ]. Therefore, in our study, we investigated the frequencies of genomic alterations and PD-L1 status in patients with primary diagnosed stage I–IIIA NSCLC to elucidate potential biomarkers for precision oncology and to explore the importance of broad-range sequencing in early tumor stages.…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, the prevalence of KRAS mutations ranges from 26 to 41%. 42 , 43 , 44 , 45 Directly targeting mutated KRAS has posed a significant challenge due to the high affinity of KRAS for GDP/GTP and the absence of identified allosteric regulatory binding sites. 46 However, in 2013, the discovery of the switch-II pocket in KRAS G12C provided a breakthrough for the development of clinically effective KRAS G12C inhibitors.…”
Section: Ema-approved Targeted Therapiesmentioning
confidence: 99%